A study of the financial reporting of the hotel industry. - Ho, Esther Hwen Chien. (2013)
In recent years, the hotel industry has expanded both in the types of business interests and in geographic span. Not surprisingly, an immense amount of financial resources, in the form of loan and capital were channeled into the industry. Investors and lenders assess the risks in acquiring shares and providing loans through the information divulged in the financial reports and other publicly available information. Unfortunately, such information becomes more difficult to interpret as the structures of hotels get more complex.